Leaf Rolling and Stem Fasciation in Grass Pea (Lathyrus sativus L.) Mutant Are Mediated through Glutathione-Dependent Cellular and Metabolic Changes and Associated with a Metabolic Diversion through Cysteine during Phenotypic Reversal - Talukdar, Dibyendu (Hindawi Publishing Corporation, 2014)
A Lathyrus sativus L. mutant isolated in ethylmethane sulfonate-treated M(2) progeny of mother variety BioL-212 and designated as rlfL-1 was characterized by inwardly rolled-leaf and stem and bud fasciations. The mutant exhibited karyomorphological peculiarities in both mitosis and meiosis with origin of aneuploidy. The mitosis was vigorous with high frequency of divisional cells and their quick turnover presumably steered cell proliferations. Significant transcriptional upregulations of cysteine and glutathione synthesis and concomitant stimulations of glutathione-mediated antioxidant defense helped rlfL-1 mutant to maintain balanced reactive oxygen species (ROS) metabolisms, as deduced by ROS-imaging study. Glutathione synthesis was shut down in buthionine sulfoximine- (BSO-) treated mother plant and mutant, and leaf-rolling and stems/buds fasciations in the mutant were reversed, accompanied by normalization of mitotic cell division process. Antioxidant defense was downregulated under low glutathione-redox but cysteine-desulfurations and photorespiratory glycolate oxidase transcripts were markedly overexpressed, preventing cysteine overaccumulation but resulted in excess H(2)O(2) in BSO-treated mutant. This led to oxidative damage in proliferating cells, manifested by severe necrosis in rolled-leaf and fasciated stems. Results indicated vital role of glutathione in maintaining abnormal proliferations in plant organs, and its deficiency triggered phenotypic reversal through metabolic diversions of cysteine and concomitant cellular and metabolic modulations.